The Chinese opera in fiction film - Tan, Sieu Chen (Universiti Malaysia Sarawak (UNIMAS), 2013)
Chinese opera in the fiction folm introduces the application of Chinese opera which its audience decline year by year, into a fictional film. The topic objectives are to identify the origins of the solo section of Chinese opera are attracted into the fiction film and determine the methods of adapting Chinese opera into fiction film such as adaptation of play, play within a play, and symbolism. The outcomes of the research will be coming out by the Chinese opera shapes the parallel structures with the fiction story in the fiction film and Chinese opera also enrich the story given by the scripwriting skills above. In the end, the researcher will practice to make a short film called Flee by Night (2013) which incorporates fiction story and Chinese opera performance.